Controls on Mineralisation Derived from Sulphur Isotopes and Trace Element Distributions in the Fraser Zone, Western Australia - Stokes, Louisa Helen (Curtin University, 2024)
This thesis investigates the controls on nickel-copper-cobalt magmatic sulphide mineralisation using sulphur isotope and trace element geochemistry in the Fraser Zone of Western Australia.